Một phương pháp xác định vị trí hiển thị thông tin phi hình học trong hệ thống thông tin địa lý - Đức, Đặng Văn; Hưng, Lê Quốc; Ngân, Trần Cẩm (Journal of Computer Science and Cybernetics, 2016)
The non-geometrical information which can be in the form of number, character string, graph on the thematic map in the GIS must be clear, readable, and balanced in geographical areas. This report presents an algorithm  for computing a number of  candidate labeling rectangles within a polygon from which a suitable selection can be made. The relevant data graph shall be within the above mentioned rectangle. This algorithm has been applied to install the PopMap for  Windows for the United Nations DEDIPA by the researchers of the IOIT.